PARTICIPATORY DEVELOPMENT OF INTANGIBLE CULTURAL HERITAGE DIGITAL DATABASE TO PROMOTE TOURISM IN PHIPUN, NAKHON SI THAMMARAT PROVINCE - Manlae, Wichian; Prathum, Boonying; Dechochai, Udomsak; Thaiklang, Suthida (Journal of MCU Nakhondhat, 2026)
This study aimed to develop a digital database of intangible cultural heritage to promote tourism in Phipun District, Nakhon Si Thammarat Province. A mixed-methods research design was employed, integrating both quantitative and qualitative approaches. For the quantitative phase, data were collected via questionnaires from a sample of 200 respondents selected through convenience sampling. This sample comprised three primary stakeholder groups: 106 tourists, 60 members of the general public, and 34 tourism entrepreneurs. The quantitative data were analyzed using descriptive statistics, including percentages, means, and standard deviations. For the qualitative phase, in-depth interviews and focus group discussions were conducted with 25 key informants selected through purposive sampling. This cohort included community leaders, local sages across five sub-districts, tourists, and active local entrepreneurs. Qualitative data were analyzed using content analysis, coding, and thematic analysis to synthesize the core themes. The findings revealed that the digital database of intangible cultural heritage for tourism promotion in Phipun District, Nakhon Si Thammarat Province, encompasses cultural capital data categorized into four primary dimensions: 1) Buddhist art and local historical heritage, 2) Local wisdom and beliefs, 3) Natural capital, and 4) Cultural management networks. Furthermore, the digital database, developed and deployed via the website www.phipun.com, covers 12 cultural heritage sites and legends by integrating a Geographic Information System (GIS) and storytelling techniques. The overall user satisfaction with the digital database was at a high level ( = 4.41) demonstrating an effective model for intangible cultural heritage management for sustainable tourism. Finally, the study synthesized a novel body of knowledge into the "P-IDE Model" and provided recommendations regarding "living cultural data" and a "digital community cultural council" to elevate and sustain the digital database.